المرأة في العالم 2010 - United Nations Department of Economic; Social Affairs (United Nations, 2010)
The World's Women 2010 uniquely reviews and analyses the current availability of data and assesses progress made in the reporting of national statistics, as opposed to internationally prepared estimates, relevant to gender concerns. Published every five years, the World's Women sets out a blueprint for improving the availability of data in the areas of demographics, health, education, work, violence against women, poverty, decision-making and human rights.